2018
DOI: 10.1155/2018/1742326
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Biomedical Waste Management in Dental Students in Different Dental Colleges in Nepal

Abstract: Aim The aim of this study is to assess the awareness of biomedical waste management in dental students of various dental colleges of Nepal. Methodology A structured pretested questionnaire was used among 434 (323 males and 111 females) undergraduate dental students of five different dental colleges of Nepal. First part of the questionnaire was used to describe demographic profile of the participants. Second part of the questionnaire assessed the knowledge, attitude, and practice regarding biomedical waste mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 12 publications
5
29
1
2
Order By: Relevance
“…As regard total attitude score levels pre and post program implementation for health care provider regarding healthcare waste management Figure 4, the present study finding showed that, pre program implementation; more than two thirds of studied subjects had negative total attitude score level.While, after program implementation the majority of them had positive total attitude score levels. This finding was in accordance with Singh et al,(2018) and found that the majority (91.82%) of participants had a positive attitude towards safe management of biomedical waste whereas less than 50% of students are aware of the guidelines laid down by Government of Nepal.…”
Section: Discussionsupporting
confidence: 88%
“…As regard total attitude score levels pre and post program implementation for health care provider regarding healthcare waste management Figure 4, the present study finding showed that, pre program implementation; more than two thirds of studied subjects had negative total attitude score level.While, after program implementation the majority of them had positive total attitude score levels. This finding was in accordance with Singh et al,(2018) and found that the majority (91.82%) of participants had a positive attitude towards safe management of biomedical waste whereas less than 50% of students are aware of the guidelines laid down by Government of Nepal.…”
Section: Discussionsupporting
confidence: 88%
“…The composition of wastes included syringes, anatomical waste, cultures, medicines, chemical wastes, rubber, gloves, tubing, swabs, gauze, pads, glasses, surgical instruments, bandage, drop-bags, cardboard, paper, wood and plastics etc. [7,8]. The biomedical wastes can potentially transmit diseases and pose an additional risk to the staff of the healthcare facilities, patients and the community as a whole, when the wastes are not managed properly using scientific and discriminate methods [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The developed countries have managed proper and sufficient infrastructure for health-care waste disposal [15,18]. A well-trained team is responsible for handling various operational procedures related to waste disposal like segregation, internal transportation and final disposal [3,8,15,18,19]. In low-income and middle countries, health-care waste generation is usually lower than in high-income countries, and there is lack of public awareness followed by improper health policy and law, and thus hospital waste is generally mixed with municipal waste [5,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations